The Effect of Medical Marijuana Laws on Labor Market Outcomes - Joseph J. Sabia; Thanh Tam Nguyen (Institute for the Study of Labor (IZA), 2016)
A number of recent studies have found that medical marijuana laws (MMLs) are associated with increased marijuana use among adults, in part due to spillover effects into the recreational market. This study is the first to explore the labor market consequences of MMLs. Using repeated cross-sections of the Current Population Survey from January 1990 to December 2014, we find that the enforcement of MMLs is associated with a 2 to 3 percent reduction in hourly earnings for young adult males. The effect is particularly pronounced when examining MMLs that include a collective cultivation provision. For women and older males, there is little evidence of adverse labor market effects of MMLs. We conclude that the health effects of MMLs may adversely affect labor market productivity of young males.
Keywords: J31; J38; I18; 330; medical marijuana laws; productivity; wages